1990
DOI: 10.1093/jnci/82.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Hyperplasia and Hyperproliferation Induced by a Nutritional Stress Diet With Four Components of Western-Style Diet

Abstract: We studied the effects of specific nutritional modifications on colonic epithelial cell proliferation in mice and rats. The nutritional stress diet developed for this study was based on the AIN (American Institute of Nutrition)-76A semisynthetic diet, modified to contain four suggested risk factors of the human Western-style diet: increased fat and phosphate and decreased calcium and vitamin D content. We fed diets to mice and rats for 12 weeks beginning at 3 weeks of age. Hyperplasia developed in both sigmoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 0 publications
5
65
0
2
Order By: Relevance
“…Our results indicated that ionized calcium cannot be used as a prognostic factor. These results agreed with Brada el al [46] and disagreed with Kristensen et al [47] as survival was found to be inversely associated with serum ionized calcium levels. It was found that elevated levels of phosphorus were necessary for adequate growth of some types of cancers [6], [7].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our results indicated that ionized calcium cannot be used as a prognostic factor. These results agreed with Brada el al [46] and disagreed with Kristensen et al [47] as survival was found to be inversely associated with serum ionized calcium levels. It was found that elevated levels of phosphorus were necessary for adequate growth of some types of cancers [6], [7].…”
Section: Discussionsupporting
confidence: 75%
“…This rise in phosphorus is due to heightened requirements of protein synthesis needed during accelerated cell growth [8]. Furthermore, a high phosphate diet has been reported to promote colonic cell hyperplasia and hyperproliferation in mice, indicating a role of Pi in carcinogenesis [47]. Elevated Pi has been suggested to promote development of cancer via amplifying Akt (also known as protein kinase B) signaling activities and enhancing cap-dependent translation, eventually resulting in increased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is a clear association between abdominal obesity, as reflected by a higher waist circumference, and colon cancer and advanced adenoma risk in both men and women (28), findings confirmed in studies where visceral fat-measured by CT scanning-was strongly associated with colorectal adenoma detection and inversely associated with circulating adiponectin levels (29). Accumulating evidence in experimental animals support these data and indicate that normal colonic epithelial cells as well as CRC cells proliferate more rapidly in obese animals and in mice fed a hypercaloric diet (30,31). Moreover, tumor development and size is increased after subcutaneous injection of CRC cells in obese compared to non-obese mice (32).…”
Section: Obesity and Colorectal Cancer Riskmentioning
confidence: 62%
“…First, it allows the accumulation of proliferating cells in the colonic crypts, it being well known that hyperproliferation coupled with hyperplasia are early morphogenetic events leading to the development of microadenomas (33,34). Under this condition, the homeostatic balance between mitotic activity and apoptosis is lost, even if the apoptotic level is higher than in normal mucosa (35).…”
Section: Discussionmentioning
confidence: 99%